Clinical Characteristics and Outcomes of Korean Patients with Lipoid Congenital Adrenal Hyperplasia: An Analysis of Data from the Multicenter Networks for Ideal Outcomes of Pediatric Rare Endocrine and Metabolic Disease (OUTSPREAD) Cohort Study - Yoonha Lee; Minsun Kim; Yun Jeong Lee; Sung Yoon Cho; Junghwan Suh; Moon Bae Ahn; Chong Kun Cheon; Chan Jong Kim; Han Hyuk Lim; Sochung Chung; Won Kyoung Cho; Eun-Gyong Yoo; et al. (Endocrinology and Metabolism, 2026)
Background: Clinical characteristics and follow-up outcomes were examined in Korean patients with lipoid congenital adrenal hyperplasia (LCAH) enrolled in the Multicenter Networks for Ideal Outcomes of Pediatric Rare Endocrine and Metabolic Disease (OUTSPREAD) cohort.Methods: Thirty-one patients (classic LCAH [C-LCAH], n=29; nonclassic LCAH [NC-LCAH], n=2) from 10 centers were included. NC-LCAH was defined by any of the following: 46,XY karyotype with male external genitalia, no fludrocortisone use, or diagnosis after infancy.Results: Median age at diagnosis was 36.5 days (interquartile range [IQR], 14.6 to 120.5); salt-wasting occurred in 58.6% of patients, and skin hyperpigmentation was the most common clinical feature (71%). All C-LCAH patients (STAR variants: p.Q258*/p.Q258* [n=27], p.Q258*/p.Arg182His [n=1], p.Q258*/p.Arg182Cys [n=1]; karyotypes: 46,XX [n=17], 46,XY [n=12]) were diagnosed in infancy with a female phenotype. Among C-LCAH patients with 46,XX, 10 had spontaneous thelarche (median, 11.0 years; IQR, 8.2 to 12.2) and five reached menarche (median, 12.4 years; IQR, 11.9 to 13.2). Among eight C-LCAH-XX patients who underwent ultrasonography, three had ovarian cysts, including one rupture. Two NC-LCAH patients (p.Q258*/p.Val187Met and p. Ala218Val/p.Gly221Ser; both 46,XY) were diagnosed at 1.6 and 3.3 years with male external genitalia; one had spontaneous puberty at 10.6 years. Eight patients reached adult height (Z-score, 0.1; IQR, −0.9 to 1.2). The hydrocortisone dose was 21.7 mg/m2 (IQR, 14.9 to 26.5) at diagnosis and 17.3 mg/m2 (IQR, 13.9 to 22.7) at last follow-up (median age, 11.6 years; IQR, 8.9 to 17.4).Conclusion: This is the first large-scale multicenter investigation in Korea reporting long-term outcomes of LCAH. Continued longitudinal follow-up focusing on pubertal development and reproductive outcomes is warranted.